A bilinear hybrid model for diauxic production of β-galactosidase by e.coli in biotechnological plants - Wolf, Martin; Storhas, Winfried; Gambier, Adrián; Badreddin, Essameddin (IEEE International Conference on Control Applications, 2007, 2007)
In this paper, a complete dynamical model for a bioprocess in pharmaceutical industry is proposed. The obtained model is bilinear and hybrid. Thus, the process forms a good application example for both, the field of bilinear systems and the field of hybrid systems. It is therefore possible to improve the control system performance by using nonlinear hybrid control techniques. Validation of the model shows satisfying results. In addition, as the model is valid for all fermentation processes and it’s derivation is performed step–by–step this paper can also serve as introductory example for teaching process modeling.